Exploring the history of Islamic Revivalism in modern Sri Lanka - Mohamed Rasak, Mohamed Arkam (IIUM Press, 2024)
This research attempts to revisit the history of Islamic Revivalism in Modern Sri Lanka highlighting the contribution of Muslims in various phases using several approaches. The objective of this paper is to explore the history of Islamic Revivalism in the context of the three primary methods adopted by Muslim intellectuals, namely, the individual approach, social movement approach, and academic institutional approach. This study uses historical, descriptive, and analytical methods. The focus of discussion in this work is on the Muslims in Sri Lanka and their individual, social movement, and academic institutional approaches to Islamic Revivalism. This paper has arrived at the conclusion that the revivalist movement among Muslims had a great influence on Sri Lanka’s community’s spiritual, social, governmental, and educational domains.